Clinical sequence of metal-ceramic fixed partial prosthesis in an aesthetic area: Case report (Research, Society and Development, 2023)
Tooth loss involves emotional, social, economic and psychological factors, which generates great impact on the individual’s health and quality of life. Removable partial dentures (RPD), implants, conventional fixed partial dentures (FPD) on teeth are used for replacing missing teeth. This study aims to report the aesthetic rehabilitation clinical sequence with Metal- ceramic Fixed Partial Dentures, describing a clinical case report, in which a female patient had tooth absence in the anterior region of the maxilla. The proposed treatment was able to return function, health and quality of life, social and psychological aspects improvement and, mainly, in well-being and elevation of self-esteem.